Leg injuries and wound repair among cosmetid harvestmen (Arachnida, Opiliones, Laniatores). (8th November 2016) - Townsend, Victor R.; Schaus, Maynard H.; Zvonareva, Tatyana; Illinik, Jeffrey J.; Evans, John T.
ABSTRACT: Previous studies of leg injuries in harvestmen have focused on the fitness consequences for individuals that use autospasy (voluntary detachment of the leg) as a secondary defense mechanism. Leg damage among non‐autotomizing species of laniatorean harvestmen has not been investigated. Under laboratory conditions, we damaged femur IV of Cynorta marginalis and observed with scanning electron microscopy (SEM) the changes in these wounds over ten days. We also used SEM to examine leg damage from individuals of three species of cosmetid harvestmen that were collected in the field. On the basis of changes in the external surface of the hemolymph coagulum, we classified these wounds as fresh (coagulum forming), recent (coagulum with smooth surface), older (coagulum is scale‐like with visible cell fragments), and fully healed (scale replaced by new cuticle growth on the terminal stump). Our observations indicate that wound healing in harvestmen occurs in a manner comparable to that of other chelicerates. Leg injuries exhibited interspecific variation with respect to the overall frequency of leg wounds and the specific legs that were most commonly damaged. In addition, we measured walking and climbing speeds of adult C . marginalis and found that individuals with fresh injuries (lab‐induced) to femur IV walked at speeds significantly slower than uninjured adults or individuals collected from the field that had fully healed wounds to a single leg. J. Morphol. 278:73–88, 2017. ©© 2016 Wiley Periodicals, Inc.